1977
DOI: 10.1126/science.831269
|View full text |Cite
|
Sign up to set email alerts
|

Marek's Disease: Effects of B Histocompatibility Alloalleles in Resistant and Susceptible Chicken Lines

Abstract: Lines of chickens selected from a common ancestral population for either resistance or susceptibility to Marek's disease developed contrasting frequencies of particular B alloalleles. Comparison of inoculated sibs in backcross-families revealed that the B alloalleles characterizing the two lines accounted for an eightfold difference in tumor incidence. This genetic difference in tumorigenesis associated with the alloalleles of the major histocompatibility complex is probably expressed through the cell-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
146
1
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(153 citation statements)
references
References 30 publications
5
146
1
1
Order By: Relevance
“…Host genetic resistance to MD was first noticed in the 1940s [16][17][18]. It was during and after the 1970s that researchers, using specialized experimental lines of chickens, identified and confirmed that major histocompatibility complex (MHC), the B-haplotypes in chicken, significantly contributes to genetic resistance against MD [19][20][21][22][23][24][25][26][27]. Soon after, genes outside of the MHC were also shown to contribute to MD resistance [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Host genetic resistance to MD was first noticed in the 1940s [16][17][18]. It was during and after the 1970s that researchers, using specialized experimental lines of chickens, identified and confirmed that major histocompatibility complex (MHC), the B-haplotypes in chicken, significantly contributes to genetic resistance against MD [19][20][21][22][23][24][25][26][27]. Soon after, genes outside of the MHC were also shown to contribute to MD resistance [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the chicken, the association between MHC polymorphism and resistance or susceptibility differences to infectious pathogens had long been recognised [13,78]. In most reports, the MHC is outlined in association to resistance or susceptibility to specific agents such as the Marek's disease virus (MDV).…”
Section: Introductionmentioning
confidence: 99%
“…MHC diversity contributes to pathogen defense in a population (34,35). Association of specific MHC haplotypes with disease resistance can be readily demonstrated in the chicken, such as B21 and resistance to Marek disease (36). Heterozygote-advantage and rare-allele advantage, or antagonistic coevolution of host and virus whereby rare alleles to which viruses have not yet adapted have an advantage (37), maintain the MHC diversity in populations.…”
mentioning
confidence: 99%